2013
DOI: 10.1364/oe.21.009365
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Yb:YCa_4O(BO_3)_3 crystal in generating high-energy laser pulses

Abstract: The passive Q-switching laser performance of Yb:YCa(4)O(BO(3))(3) is studied with crystals cut along the principal optical axes. Using a Cr(4+):YAG saturable absorber with initial transmission of 93.7% and an output coupler of transmission of 40%, efficient Q-switched laser operation is achieved with a X-cut crystal, generating an output power of 2.14 W at a pulse repetition rate of 4.5 kHz. The resulting laser pulse is 9.3 ns in duration, with the energy being as high as 476 μJ and the peak power amounting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Such a situation seems to be entirely different from any other passively Q-switched Yb lasers demonstrated in our previous work. [6] In this Letter, we report on our experimental results obtained with a Yb:YVO 4 laser passively Qswitched by a Cr 4+ :YAG saturable absorber, which proved to be quite different from the previously reported results. According to our experiment, only with a Cr 4+ :YAG saturable absorber having an initial transmission (𝑇 0 ) as high as 𝑇 0 = 99.3%, could stable passively Q-switched operation be achieved with a Yb:YVO 4 crystal laser, in which no Raman selfconversion is observed.…”
contrasting
confidence: 62%
“…Such a situation seems to be entirely different from any other passively Q-switched Yb lasers demonstrated in our previous work. [6] In this Letter, we report on our experimental results obtained with a Yb:YVO 4 laser passively Qswitched by a Cr 4+ :YAG saturable absorber, which proved to be quite different from the previously reported results. According to our experiment, only with a Cr 4+ :YAG saturable absorber having an initial transmission (𝑇 0 ) as high as 𝑇 0 = 99.3%, could stable passively Q-switched operation be achieved with a Yb:YVO 4 crystal laser, in which no Raman selfconversion is observed.…”
contrasting
confidence: 62%
“…In addition, RECOB crystals are reported to be excellent laser host materials for self-frequency doubling and ultrafast laser applications. [17][18][19][20][21][22][23][24] Particularly, the large-sized YCOB crystal is deemed a powerful candidate for optical parametric chirpedpulse amplification (OPCPA) systems. [25][26][27][28] Previous studies have also revealed that the partial substitution of Y 3+ ions in the YCOB crystal by other RE cations with larger ionic radii could lead to a smaller optical birefringence.…”
Section: A Introductionmentioning
confidence: 99%
“…Sci. 2021, 11, 10879 2 of 14 Yb 3+ :Gd 3 Ga 5 O 12 (GGG) [20], (Yb x Y 1−x ) 3 (Sc 1.5 Ga 0.5 )Ga 3 O 12 (YSGG) [21], Yb 3+ :Lu 3 Ga 5 O 12 (LuGG) [22]), tungstates (e.g., Yb 3+ :KGd(WO 4 ) 2 (KGW) [23,24], Yb 3+ :NaY(WO 4 ) 2 (NaYW) [25], Yb 3+ :NaGd(WO 4 ) 2 (NaGdW) [26], Yb 3+ :KLu(WO 4 ) 2 (KLuW) [27]), and borates (Yb 3+ :YCa 4 O(BO 3 ) 3 (YCOB) [28][29][30], Yb 3+ :GdCa 4 O(BO 3 ) 3 (GdCOB) [28,31]). Among them, Yb 3+ -doped borates with short bond lengths (e.g., Yb:YCOB and Yb:GdCOB) have relatively smaller emission cross-sections (~0.5 × 10 −20 cm 2 ), longer fluorescence lifetimes (~2 ms), broader emission spectra (45 nm), and have been proven to be excellent energy storage materials.…”
Section: Introductionmentioning
confidence: 99%